Survival of Human Dental Plaque Flora in Various Transport Media - Syed, Salam A. (1972)
Dental plaque samples from (i) subjects with no apparent oral disease, (ii) mentally retarded subjects with periodontal disease, and (iii) subjects with active caries were collected in three transport media viz. a dithiothreitol poised balanced mineral salt solution designated as reduced transport fluid (RTF), VMG II, and modified Stuart medium (SBL). The samples were dispersed by sonic treatment, diluted in the respective medium in which they were collected, and cultured on MM10 sucrose agar. The efficiency of the transport media in the survival of dental plaque flora was determined by comparing the quantitative recovery (expressed as percentage of the initial viable count) from the specimens stored for various lengths of time. The data showed a great variation in the recovery of the oral bacterial flora from the plaque samples. VMG II and SBL served better than RTF as storage media for non-disease-associated dental plaque cultured under strict anaerobic conditions. Recoveries of bacteria from periodontal plaque specimens stored in RTF were higher than SBL and VMG II under identical conditions. The organisms present in the carious plaque samples appeared to survive much better in RTF and VMG II than in SBL as determined by conventional anaerobic culturing technique. However, VMG II showed a higher recovery of organisms from these specimens with an increase in the storage period, suggesting multiplication of the plaque flora. RTF did not allow the growth of oral bacterial flora under all experimental conditions. On the basis of the relative performance of these media it is suggested that RTF is a satisfactory medium for the transport of oral bacteria present in the samples.